Challenge of capturing socially generated land values: principle versus practicality. Issue 6 (1st November 2020) - Jones, Colin; Stephens, Mark
Abstract : This article provides a review of past attempts to harness the uplift in land values arising from granting planning permission to better understand the current difficulties of the use of land-value capture. The scheme has been the most successful approach to date, but the theoretical fundamentals are fudged and there are substantial policy variations between localities: a victory of practicality over principle. We argue that a tax on development value would be more effective whilst maintaining the principles of taxing socially generated land values.